ANALISIS GAYA BAHASA DALAM KUMPULAN PUISI KEKASIHKU KARYA JOKO PINURBO: KAJIAN STILISTIKA - Lisa Widyaningsih (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Poetry still exists today, through poetry the author can express his feelings and thoughts. In addition to being written, poetry can also be read, made into musicals, inserted in short stories, novels, and films. There are various studies that can be used to analize poetry, one of which is stylistics studies. Tyhrough this study, it can be seen the style of language used by the author in making poetry. The purpose of this study is to find the style of language in the collection of poems My Firl by Joko Pinurbo. This study uses a qualitative method. Data analysis was carried out using Miles and Huberman analysis techniques, namely data reduction, data presentation, and drawing conclusions. The result of the research on the use of language styles in the collection of poems My Girl by Joko Pinurbo, namely parable language style, metaphor language style, personification language style, cynicism style, and anaphoric language style.Keywords: literary works; poetry; stylistics